Pelaksanaan Ekstrakurikuler Seni Tari di SMA Negeri 1 Mandau Kabupaten Bengkalis Provinsi Riau - Vhasya Amanda Putri; Susmiarti Susmiarti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to find out the Implementation of Dance Arts Extracurricular at SMA Negeri 1 Mandau, Bengkalis Regency, Riau Province. This type of research is qualitative research with the method used, namely descriptive. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze the data are data collection, data reduction, data display and conclusion drawn. The results of the study show that the Dance Arts Extracurricular Planning at SMA Negeri 1 Mandau has been well coordinated according to the program made by the Supervisor starting from the schedule, time and objectives of the program. The implementation of Dance Arts Extracurricular at SMA Negeri 1 Mandau is held 8 times, namely 2 times a week on Fridays and Saturdays. The implementation of Dance Arts Extracurricular at SMA Negeri 1 Mandau can run well and try its best in carrying out dance extracurricular arts according to the schedule, but there are inadequate facilities and some students are not disciplined. This obstacle can certainly be an obstacle in the implementation of dance extracurriculars, but this problem can still be overcome. In addition, the motivation provided by the teacher can encourage the enthusiasm and enthusiasm of students in every meeting.